1998
DOI: 10.1051/aas:1998417
|View full text |Cite
|
Sign up to set email alerts
|

A radio continuum study of the Magellanic Clouds

Abstract: Abstract. We present a study of discrete radio sources in the Magellanic Clouds (MCs) using the latest large-scale radio surveys made with the Parkes radio telescope between 1.4 and 8.55 GHz. These surveys achieved higher sensitivity then previous surveys done with the Parkes telescope and so the number of discrete radio sources detected towards the MCs has increased by factor of five. Also, we have obtained improved positions, flux densities and radio spectral indices for all of these sources.A total of 483 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 58 publications
(85 reference statements)
5
113
0
Order By: Relevance
“…Filipovic et al (1998) used Parkes surveys to study the radio spectral index and luminosityy distribution of 34 confirmed and 24 probable LMC SNRs. Williams et al (1999a) were the first to study the X-ray morphology of all known LMC SNRs at that time.…”
Section: Literature Surveymentioning
confidence: 99%
“…Filipovic et al (1998) used Parkes surveys to study the radio spectral index and luminosityy distribution of 34 confirmed and 24 probable LMC SNRs. Williams et al (1999a) were the first to study the X-ray morphology of all known LMC SNRs at that time.…”
Section: Literature Surveymentioning
confidence: 99%
“…Note log−log scale. from SNR J0530-7007 was estimated to be α T = −0.85 ± 0.13, while the typical SNR spectral index is α = −0.5 ± 0.2 (Filipović et al 1998). This somewhat steeper spectral index would indicate a younger age despite its (large) size of 52 × 44 pc, suggesting it as an older (more evolved) SNR.…”
Section: Resultsmentioning
confidence: 99%
“…However, the environment in which the SNR evolves i.e. the interstellar medium (ISM) with its ambient magnetic field, will not only affect the radio spectral index observed but also the SNR's morphology, structure and behaviour (Filipović et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If X-ray radiation was detected from the intrinsic source, then it was classified as a SNR candidate since the violent explosions and shockwaves produced by a supernova are known to emit strong X-rays. Also, SNRs usually exhibit steeper spectral index of about α < −0.5 (Filipovic et al 1998). Sources emitting infrared radiation but no detectable X-rays were classified as H ii regions.…”
Section: Discrete Sources Within the Field Of Ngc 55mentioning
confidence: 99%